Professionalisation as a Moral Concern - Louw, Johan (PINS-Psychology in Society, 2025)
"We reject … the whole idea of 'experts' and professionals holding forth on how we should accept our disabilities or giving learned lectures about the psychology of disablement. We already know what it feels like to be poor, isolated, segregated, done good to, stared at, and talked down to - far better than any able-bodied expert. We as a Union are not interested in descriptions of how awful it is to be disabled. What we are interested in are ways of changing our conditions of life, and thus overcoming the disabilities which are imposed on top of our physical impairments by the way society is organized to exclude us. … We look forward to the day when the army of ‘experts’ on our social and psychological problems can find more productive work." This quote is from the policy statement, of the Union of Physically Impaired Against Segregation in Britain (Hales, 1982). It reflects a point of view that in recent years has found more and more support, namely that professionalisation is not without its hazards in society. This paper follows this tradition of unease about the effects of increasing professionalization of large sections of modern society. It is concerned with professionalization as a general phenomenon, and not with South Africa in particular. I believe, however, that South African psychologists will recognise very readily how these considerations directly touch upon the growth of the discipline in this country. No prescriptions or guidelines as to how to proceed from here are offered, but Andy Dawes (1986) presented a number of specific local suggestions, while Hales gave three examples of an "alternative" use of professional expertise. Finally, I do not claim too much originality for the arguments advanced here: as the references will indicate, I drew heavily on the work of Bledstein, Geuter, Habermas and Gouldner.